ANALISIS PENERAPAN STRATEGI SEGMENTING, TARGETING DAN POSITIONING TERHADAP TABUNGAN PRIMA IB BANK TABUNGAN NEGARA SYARIAH PROBOLINGGO - Halima, Halima; Nasrifah, Maula; Admati, Anat (universitas Islam Zainul Hasan Genggong, 2024)
This research aims to find out how the segmenting, targeting and positioning (STP) strategy is implemented in a company, where the STP strategy itself has an important role in increasing a company's profits from iB prime savings at Bank Tabungan Negara Syariah Probolinggo (BTN). This method uses qualitative methods in collecting interview data (In-depth interviews), focus group discussions (FGD) and is equipped with documentation carried out with 3 sources, namely customer service and 2 members of the finance office of BTN Syariah Probolinggo bank. The results of this research show that the Prima iB Savings at BTN Syariah Bank Probolinggo applies the STP strategy to its products. Implementation of segmentation for Prima iB Savings through geographic, behavioral and democratic segmentation. Meanwhile, targeting is applied to entrepreneurs, developers and notaries because the target market itself is customers from the upper middle class economy because they have quite high mobility. Finally, the application of positioning 1. Social media 2. Large events 3. Through verbal 4. Bank BTN Syariah Probolinggo marketing. This research is equipped with obstacles and solutions to overcome problems that exist in a company in the Prima iB Savings product.